PELESTARIAN KEBUDAYAAN LOKAL DALAM PERMAINAN TRADISIONAL MELALUI FAN DI PANTAI PURUS KOTA PADANG - Najeli Engla Haryasa; Lili Dasa Putri (Jurusan Pendidikan Masyarakat Fakultas Keguruan Ilmu Pendidikan Universitas Siliwangi, 2022)
AbstractFAN stands for Festival Anak Nagari which is a work program from Adwindo Padang City. This program aims to increase the interest and knowledge of the community, especially children, to traditional games and to revive Minang culture. This Nagari Children Festival can help the community, especially children and teenagers in the purus beach area of Padang City to remember and recognize traditional games that have long faded among them, because over time the local culture in an area will fade if there is no preservation of the culture. As has happened in the purus beach area of Padang City where there are still many people, especially children and teenagers who have forgotten games such as congklak, cakbur, lompek kajai and so on which are caused by online games, because they feel more practical in playing them. The method used in this article is a literature study by citing and reading books or websites related to the titles made in this article. (Zed,2008:3). The results found in the field explain that the preservation of local culture in traditional games through FAN in Padang City is going very well and has a positive impact on preserving local culture in the city of Padang. Because many people who take part in this activity have remembered what traditional games they had forgotten before.Â Â